Update breast cancer 2020 part 4 - advanced breast cancer = Update Mammakarzinom 2020 Teil 4 – fortgeschrittenes Mammakarzinom - Tesch, Hans; Müller, Volkmar; Wöckel, Achim; Ettl, Johannes; Belleville, Erik; Schütz, Florian; Hartkopf, Andreas; Thill, Marc; Huober, Jens; Fasching, Peter A.; Kolberg, Hans-Christian; Schulmeyer, Carla E.; et al. (Geburtshilfe und Frauenheilkunde, 2020)
Substances with good effectiveness that intervene in specific signalling pathways have been used increasingly in recent years in the treatment of patients with advanced breast cancer, and new therapies and approaches have now been added, which actually relate to quite specific changes, such as the treatment of patients with HR+/HER2 tumours with a PIK3CA mutation. The treatment of patients with a BRCA1or BRCA2 mutation has also been improved by the introduction of PARP inhibitors. Attempts are now being made increasingly to extend treatment indications based on molecular patterns, to identify other patients who could benefit from a treatment and to integrate the newly established treatment methods in existing therapy sequences. This review articles summarises the latest information in this connection.
Gesehen am 12.02.2021